Different training methods cause similar muscle damage in youth judo athletes - Derek, A.; Karnincic, H.; Franchini, E.; Krstulovic, S.; Kuvacic, G. (Journal of Human Kinetics, 2021)
It is well known that different factors can contribute to muscle damage in judo matches or training. Previous research analyzed only the effects of simulated judo combat or judo training on biochemical markers of muscle damage without determining its specific causes. Our objective was to identify possible differences in biochemical markers of muscular damage in response to different training methods in youth judo athletes. Twelve high-level male judo athletes ere randomly assigned to a standing (SP, n = 6, age = 16.6 ± 1.1 years) or a groundwork (GP, n = 6, age = 17.8 ± 0.8 ears) position combat practice group. Both groups had the same protocol of four 4-minute combat practice bouts separated by 1-minute rest intervals. Before and immediately after combat practice blood samples were taken to assess muscle damage markers : creatine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST) and alanine aminotransferase (ALT). There were significant increa ses in AST, LDH, and CK after the standing and groundwork training sessions compared with resting values in both groups. Additionally, no significant differences in the enzyme's activity between SP and GP groups were fo und. These results showed that standing and groundwork randori training (free sparring or free practice) causes similar muscle damage in adolescent judo athletes. Future research should assess the effects of the same damage mechanisms over a longer period of time.